Las nuevas tecnologías en la enseñanza y aprendizaje de la matemática (ING) - Poveda, Ricardo (2003)
Technology changes today more than it ever did in human history. Its impact is felt in all fields of human activity, particularly in education. This paper gives an account of some modern technologies, more or less available or potentially available, in educational institutions. Current uses are also briefly reviewed, as well as difficulties in their implementation and widespread adoption. These comments emphasize graphical calculators and computers.